2017
DOI: 10.1016/j.neurobiolaging.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Successful optic nerve regeneration in the senescent zebrafish despite age-related decline of cell intrinsic and extrinsic response processes

Abstract: Dysfunction of the central nervous system (CNS) in neurodegenerative diseases or after brain lesions seriously affects life quality of a growing number of elderly, since the adult CNS lacks the capacity to replace or repair damaged neurons. Despite intensive research efforts, full functional recovery after CNS disease and/or injury remains challenging, especially in an aging environment. As such, there is a rising need for an aging model in which the impact of aging on successful regeneration can be studied. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 65 publications
9
31
0
Order By: Relevance
“…As described above, an elegant recent study (Ferrero et al, 2018), showed the existence of a second wave of re-population of the brain’s microglia, which originate from HSCs – a process that occurs between 2 weeks and 3 months of age. Microglia can be detected by L-plastin (or LCP-1), a pan-leukocyte marker (Redd et al, 2006; Cvejic et al, 2008; Mathias et al, 2010; Van Houcke et al, 2017), by macrophage-expressed gene 1 ( mpeg1 ), labeling all mononuclear phagocytes (Ellett et al, 2011; Wittamer et al, 2011), by the 4c4 antibody (Becker and Becker, 2001)as well as Apolipoprotein E (ApoE) [Oosterhof et al (2015), see Table 1; Figure 1]. Note that, although ApoE specifically labels microglia if compared with the other markers mentioned, it has also been shown to be expressed astrocytes (Boyles et al, 1985; Poirier et al, 1991; Xu et al, 2006), oligodendrocytes (Stoll et al, 1989), as well as by some neurons albeit at lower levels (Han et al, 1994; Achariyar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, an elegant recent study (Ferrero et al, 2018), showed the existence of a second wave of re-population of the brain’s microglia, which originate from HSCs – a process that occurs between 2 weeks and 3 months of age. Microglia can be detected by L-plastin (or LCP-1), a pan-leukocyte marker (Redd et al, 2006; Cvejic et al, 2008; Mathias et al, 2010; Van Houcke et al, 2017), by macrophage-expressed gene 1 ( mpeg1 ), labeling all mononuclear phagocytes (Ellett et al, 2011; Wittamer et al, 2011), by the 4c4 antibody (Becker and Becker, 2001)as well as Apolipoprotein E (ApoE) [Oosterhof et al (2015), see Table 1; Figure 1]. Note that, although ApoE specifically labels microglia if compared with the other markers mentioned, it has also been shown to be expressed astrocytes (Boyles et al, 1985; Poirier et al, 1991; Xu et al, 2006), oligodendrocytes (Stoll et al, 1989), as well as by some neurons albeit at lower levels (Han et al, 1994; Achariyar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the first model, the nerve is cut with scissors, thereby creating a proximal and distal nerve stump that are physically separated from each other. In contrast, in the ONC model, the nerve is crushed with forceps to separate the axons, but leaving the connective tissue around them intact, and thus holding the proximal and distal ends together (Becker et al 2000;McCurley and Callard 2010;Fleisch et al 2011;Lemmens et al 2015;Van Houcke et al 2017). As expected, the ONT model is somewhat more drastic and regeneration progresses slower as compared to ONC (Zou et al 2013).…”
Section: Models and Methods To Study Spontaneous Optic Nerve Regeneramentioning
confidence: 96%
“…To culture fish retinal explants, retinas are chopped into small squares and transferred to poly-L-lysine-coated well plates. After an incubation period of 1-4 days, the number of neurites, their length and/or density can be quantified (Becker and Becker 2002;Becker et al 2004;Veldman et al 2007Veldman et al , 2010Elsaeidi et al 2014;Ogai et al 2014;Welte et al 2015;Van Houcke et al 2017). …”
Section: Ex Vivo Tissue Explant Studies In Other Vertebratesmentioning
confidence: 99%
See 2 more Smart Citations